2020
DOI: 10.3390/ijms21197224
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Beta Dehydratase in the Lipid Biosynthesis Pathway Is Required for Conidiogenesis, Pigmentation and Appressorium Formation in Magnaporthe oryzae S6

Abstract: Lipid biosynthesis produces glycerol, which is important in fueling turgor pressure necessary for germination and penetration of plant host by fungi. As the relationship between pathogenicity and the lipid biosynthetic pathway is not fully understood, we have elucidated the role of the fatty acid synthase beta subunit dehydratase (FAS1) gene in lipid biosynthesis. The FAS1 gene was silenced through homologous double crossover in Magnaporthe oryzae strain S6 to study the effect on lipid biosynthesis. The vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…Finally, the switch to necrotrophic growth by M. oryzae is represented by M8, M9 and M10, which peak in expression after 72hpi (Figure 2B). These modules include gene functions associated with conidiogenesis, such as SMO1 , encoding a Ras GTPase-Activating Protein, the fatty acid synthase beta subunit dehydratase FAS1 (Sangappillai and Nadarajah, 2020) and the necrosis- and ethylene-inducing protein 1-encoding gene NLP1 (Park et al, 2006; Fang et al, 2017; Kershaw et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the switch to necrotrophic growth by M. oryzae is represented by M8, M9 and M10, which peak in expression after 72hpi (Figure 2B). These modules include gene functions associated with conidiogenesis, such as SMO1 , encoding a Ras GTPase-Activating Protein, the fatty acid synthase beta subunit dehydratase FAS1 (Sangappillai and Nadarajah, 2020) and the necrosis- and ethylene-inducing protein 1-encoding gene NLP1 (Park et al, 2006; Fang et al, 2017; Kershaw et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition we observed the change in the morphology of the fungal mycelium of both isolates (Fig. 2 B), which directly re ects in the pathogenicity of the fungus when in contact with the plant (Sangappillai and Nadarajah 2020) and also the reduction of up to 62% in the production of conidia of B oryzae.…”
Section: Discussionmentioning
confidence: 82%
“…In M. oryzae , an MoMFP1 ( FOX2 , a multifunctional enzyme) deletion prevented the utilization of fatty acids as the sole carbon source and attenuated M. oryzae virulence ( Wang et al, 2007 ). Furthermore, the fatty acid synthase β - subunit dehydratase Fas1 is essential for peroxisome biogenesis, β-oxidation, and pathogenesis ( Sangappillai and Nadarajah, 2020 ). Consistent with these findings, our data showed that deletion of MoPCS60 led to defects in the utilization of long-chain fatty acids, peroxisome biogenesis, and infectious growth in M. oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…In M. oryzae , lipid droplets move to the appressorium following conidial germination. Lipid droplet degradation is associated with glycerol accumulation, which is required for generating turgor pressure during penetration ( Wang et al, 2007 ; Sangappillai and Nadarajah, 2020 ). Although the Δ Mopcs60 mutant exhibited defects in fatty acid metabolism and virulence, the mobilization and breakdown of lipid droplets during turgor generation were not impaired in the appressorium; this is in contrast to the mutants Δ Momfp1 , Δ far1 , Δ far2 , and Δ far1 Δ far2 ( Wang et al, 2007 ; bin Yusof et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%